2016
DOI: 10.1073/pnas.1605509113
|View full text |Cite
|
Sign up to set email alerts
|

A conserved amino acid residue critical for product and substrate specificity in plant triterpene synthases

Abstract: Triterpenes are structurally complex plant natural products with numerous medicinal applications. They are synthesized through an origami-like process that involves cyclization of the linear 30 carbon precursor 2,3-oxidosqualene into different triterpene scaffolds. Here, through a forward genetic screen in planta, we identify a conserved amino acid residue that determines product specificity in triterpene synthases from diverse plant species. Mutation of this residue results in a major change in triterpene cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 57 publications
1
63
2
Order By: Relevance
“…These enzymes produce tetracyclic and pentacyclic triterpenes from the same protosteryl‐type C‐B‐C conformation (Banta et al ., ). Studies (Ito et al ., ; Salmon et al ., ) on Euphorbia tirucalli and Avena strigosa β ‐ amyrin synthase (SAD1) have identified two conserved residues at positions F696 and S699 (positions of HsLAS) which, when mutated, result in a change in product from the pentacyclic triterpenoid β ‐ amyrin to tetracyclic cyclization products, but maintain a dammarane‐type C‐C‐C conformation. The three key residue positions, #124, #365 and #732, in OsPS and OsOS, corresponding to L104, I335 and I702 in HsLAS, that have been identified here were not reported in the previous studies (Ito et al ., ; Banta et al ., ; Salmon et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes produce tetracyclic and pentacyclic triterpenes from the same protosteryl‐type C‐B‐C conformation (Banta et al ., ). Studies (Ito et al ., ; Salmon et al ., ) on Euphorbia tirucalli and Avena strigosa β ‐ amyrin synthase (SAD1) have identified two conserved residues at positions F696 and S699 (positions of HsLAS) which, when mutated, result in a change in product from the pentacyclic triterpenoid β ‐ amyrin to tetracyclic cyclization products, but maintain a dammarane‐type C‐C‐C conformation. The three key residue positions, #124, #365 and #732, in OsPS and OsOS, corresponding to L104, I335 and I702 in HsLAS, that have been identified here were not reported in the previous studies (Ito et al ., ; Banta et al ., ; Salmon et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the peak corresponding to tetracyclic triterpenols was of greater area (Figs b, S5). The peak at 23.9 min was identified as cycloartenol by comparison with the authentic cycloartenol standard, and one minor peak at 28.0 min was identified as a putative damarenediol‐II by comparison of its mass fragmentation pattern with a prior report (Salmon et al ., ). These results suggest the importance of both residues for pentacyclic cyclization by BfOSC3.…”
Section: Resultsmentioning
confidence: 97%
“…These results suggest the importance of both residues for pentacyclic cyclization by BfOSC3. Similar results have been reported previously for SAD1 (β‐amyrin synthase from Avena strigosa ), which transformed enzyme activity (from mainly producing pentacyclic products to mainly producing tetracyclic products) via a single mutation at S728F (Salmon et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Recently, another study describing mutants of the β-amyrin synthase SAD1 from Avena strigosa identified that the mutation Cys563Tyr block initiation of cyclization48. This is the third residue involved with initiation of cyclization so far, since both catalytic aspartic acid and the highly conserved cysteine of the DCTAE motif have previously been demonstrated to be essential for enzymatic activity4950.…”
Section: Resultsmentioning
confidence: 99%
“…Using protein modelling and docking analysis, as performed herein, that work predicted that, in the SAD1 β-amyrin synthase Ser728Phe mutant, the large aromatic side chain of phenylalanine in position 728 interferes with the Phe725, of the catalytic centre, resulting in an interruption of ring expansion of the dammarenyl cation and leading to the formation of truncated tetracyclic oxidosqualene cyclization products. Moreover, the SAD1-Ser728Phe and AtLUP1-Thr729Phe mutants preferentially accepts dioxidosqualene as a substrate when expressed in yeast and cyclizes this to epoxydammarane derivatives, which suggests that Ser728 also affects the ability of the possible OSC substrates to access the active site48.…”
Section: Resultsmentioning
confidence: 99%